Important ornamental plants of Bharatpur Metropolitan City, Nepal - Das, Manoj K.L. (BMC Journal of Scientific Research, 2022)
The practices of decorating home gardens and public places by ornamental plants have been known from ancient time. The present study was destined to document about the circumstances of ornamental plants in Bharatpur Metropolitan City. Informations were collected by questionnaires, interview and direct observation. 90 ornamental plants were documented belonging to 49 families. Out of them, 42 plants belong to the herbs, 28 plants are shrubs, 14 plants are trees and 3 plants of each were represented as climbers and epiphytic herbs respectively. 59 plants were cultivated for flowers. The most dominant ornamental plants are Tagetes patula (saypatri) Rosa indica (rose), Hibiscus rosa sinensis (Ghanti phool) Bougainvellia glabra (Kagaje phool) and Aloe vera (Gheu Kumari). The Plate families like Malvaceae, Asteraceae, Apocyanaceae, Fabaceae and Euphorbiaceae are frequently found in study area.